Prevalence and pathogen load of Campylobacter spp., Salmonella enterica and Escherichia coli O157/O145 serogroup in sheep faeces collected at sale yards and in abattoir effluent in Western Australia. Issue 5 (May 2017) - Yang, R; Abraham, S; Gardner, GE; Ryan, U; Jacobson, C
Abstract : Objective: Develop a multiplex quantitative PCR assay to investigate the prevalence and shedding of Escherichia coli O157/O145, Salmonella spp. and Campylobacter spp. in sheep at sale yards and abattoirs. Methods: A qPCR for E. coli O157/O145 was developed, validated and multiplexed with an existing qPCR for Campylobacter and Salmonella enterica . The absolute numbers of E. coli O157/O145, Campylobacter and Salmonella in control samples was determined using droplet digital PCR. These were then used as the controls in the multiplex qPCR on a total of 474 sheep faecal samples collected from two saleyards over a 4‐month period (April–July 2014) and 96 effluent samples from an abattoir. Results: The mutiplex qPCR was specific with a sensitivity of 5 organisms/μL faecal DNA extract for Campylobacter, S. enterica and E. coli O157/O145. The overall prevalence of Campylobacter, S. enterica and E. coli O157/O145 in faecal samples was 5.7%, 3.6% and 8.4% and in effluent samples was 18.8%, 6.3% and 5.2%, respectively. The pathogen loads of Campylobacter, S. enterica and E. coli O157/O145 in faecal and effluent samples was also determined via mutiplex qPCR. Conclusions: The overall prevalences of Campylobacter, S. enterica and E. coli O157/O145 were generally low (<6%), but point prevalences ranged considerably in healthy sheep (up to 26% for E. coli O157/O145). Further work to determine risk factors for shedding of bacterial organisms in meat sheep in the pre‐slaughter period (on‐farm, sale yards and lairage at abattoirs) could further reduce the risk of contamination of meat products.